STUDI KOMPARASI KMA NO. 183 TAHUN 2019 DENGAN KMA NO. 165 TAHUN 2014 TENTANG PEDOMAN KURIKULUM 2013 MATERI PAI DAN BAHASA ARAB - MOCHAMMAD SHOFWAN HIDAYATULLOH; MARDIYAH MARDIYAH (CENDEKIA: Jurnal Ilmu Pengetahuan, 2022)
In the world of education, it is very common for curriculum changes to be carried out with various considerations in accordance with changing times. In line with changes in the curriculum in Indonesia, the Ministry of Religion also issued a new curriculum written in KMA No. 183 of 2019 replacing KMA No. 165 of 2014 concerning 2013 curriculum guidelines for PAI and Arabic language materials. In KMA No. 165 of 2014 and KMA No. 183 of 2019, it is stated that the basic framework of the Madrasah Curriculum (PAI and Arabic) has been developed on philosophical, sociological, psycho-pedagogical, and juridical basis. Regarding the assessment of PAI and Arabic, KMA No. 183 of 2019, still has some similarities with KMA No. 165 of 2014, among others, assessment objectives, assessment principles, assessment methods, assessment techniques and tools as well as assessment aspects (attitudes, knowledge and skills). However, the highlight of KMA No. 183 of 2019 is the assessment of aspects of knowledge that require higher-order thinking skills or HOTS which has never been discussed at KMA No. 165 of 2014 before. ABSTRAKDalam dunia pendidikan sangat lumrah jika perubahan kurikulum terus dijalankan dengan berbagai pertimbangan sesuai dengan perubahan zaman. Sejalan dengan perubahan kurikulum di Indonesia, Kementerian Agama juga mengeluarkan kurikulum baru yang tertulis dalam KMA No. 183 tahun 2019 menggantikan KMA No. 165 tahun 2014 tentang pedoman kurikulum 2013 materi PAI dan Bahasa Arab. Dalam KMA No. 165 Tahun 2014 dan KMA No. 183 Tahun 2019, disebutkan bahwa kerangka dasar Kurikulum Madrasah (PAI dan Bahasa Arab) telah dikembangkan atas dasar falsafah, sosiologi, psiko-pedagogis, dan yuridis. Terkait penilaian PAI dan Bahasa Arab, KMA No. 183 Tahun 2019, masih memiliki beberapa kesamaan dengan KMA No. 165 Tahun 2014, antara lain tujuan penilaian, prinsip penilaian, metode penilaian, teknik dan alat penilaian serta aspek penilaian (sikap, pengetahuan dan keterampilan). Namun yang menjadi sorotan dari KMA No 183 Tahun 2019 ini adalah penilaian aspek pengetahuan yang membutuhkan kemampuan berpikir tingkat tinggi atau HOTS yang belum pernah dibahas di KMA No 165 Tahun 2014 sebelumnya.